Hipsterism A Paradigm for Modernity - Semple, Tara (Kultur und gesellschaftliche Praxis,, 2023)
This Open-Access-book utilises Hipsterism to demonstrate modes of identity, collectivity, conceptions and a whole spectrum of activities with varying degrees of commitment in contemporary society. Analysed through the lens of Modernity, Consumerism, and the New Spirit of Capitalism, it draws on qualitative research from two subsequent field stays in Berlin and is complemented by self-reflexion within the field. Young adults and their conceptions within modernity, capitalism and consumerism constitute a fundamental building block to understanding society. Little sociological work has been done in the field of Hipsterism, although it can function as a paradigm for western, affluent societies. With tools such as conscious consumption, conversations and ethical or creative work within a politically intended lifestyle, Hipsterism emerges as an attempt to navigate between individualism and collectivity. Resulting from these circumstances are a variety of forms of action, while searchingfor better ways to contribute and engage at the same time. Attempts to dissolve milieus and try to construct spaces where different cultures, classes and ethnicities are welcome might fail in spatial practice, but the practices in sum still leave a trace in (consumer) culture. All these activities hint at the potential of transformative and negotiating power that Hipsterism could have. About the Author Tara Semple first observed Hipsters in New York when she spent some months at the United Nations. She maintained a keen interest in the analysis of modern capitalism and influences on young adults in her work in academia and as a journalist, currently based in Zurich.